Implementasi Sistem Peradilan Koneksitas Dalam Perkara Tindak Pidana Korupsi Di Badan Pengelola Tabungan Wajib Perumahan Angkatan Darat - Margareth Trisya Adefinola Naru; Boedi Prasetyo (LPPM STAI Muhammadiyah Probolinggo, 2025)
The corruption case in the Army Housing Compulsory Savings Management Agency (BPTWP-AD) is one of the connected justice systems that is implemented transparently and fairly to prevent the recurrence of corruption in the military environment carried out together with civilians. This case highlights the challenges faced by the Indonesian justice system, where corruption not only harms state finances but also threatens public trust in government institutions. The connected justice system emerged as a solution to integrate the legal process in cases involving collusion between military and civilian officials, which shows the complexity and challenges in law enforcement in Indonesia. The focus of the research is based on relevant laws and regulations, including the Law on Criminal Procedure and the Law on Military Justice, as well as the legal principles governing criminal liability. Legal document analysis was conducted to dig deeper into related legal documents, such as court decisions, investigation reports, and other documents. This method helps in understanding the flow of the legal process and the application of the connected justice system in the cases studied. The application of the connected justice system has succeeded in integrating the legal process between military and civilian actors, demonstrating efficiency and transparency in handling corruption cases that result in state losses. However, challenges such as coordination between military and civilian institutions and differences in legal procedures still need to be overcome to ensure justice